IMPLEMENTATION OF SERVICE STRATEGIES IN INCREASING MEMBER SATISFACTION AT KSPPS NURI PAKONG BRANCH - Hidayat, Ach.Tauﬁq; Sohib, Sohib; Anas, Achmad Tarmidzi (LP2M IAI Al-Khairat Pamekasan, 2023)
This study aims to analyze the implementation of service strategies in increasing member satisfaction at the KSPPS NURI Pakong Branch. A good service strategy is key to maintaining and increasing member satisfaction, which in turn can strengthen loyalty and trust in the institution. This study uses a descriptive approach with a qualitative method, where data is collected through interviews, observations, and documentation studies. The results of the study show that the implementation of the service strategy at KSPPS NURI Pakong Branch has been quite effective in increasing member satisfaction. This is reflected in the improvement in the quality of interaction between officers and members, the speed of service, and the ease of accessing services. However, there are still several aspects that need to be improved, such as service consistency and improving human resource competence. These findings provide insight for KSPPS NURI to continue to improve and optimize its service strategy to achieve higher member satisfaction.